Reproductive characteristics of Liza parsia (Ham.) inhabiting southwest coast of Bangladesh (Journal of the Bangladesh Agricultural University, 2010)
In order to determine the reproductive characteristics of Liza parsia, a fish of commercial importance, the GSI, egg diameter, sex ratio and fecundity were examined in 331 specimens caught monthly for a period of ten months from September 2006 to June 2007. According to the GSI and egg diameter, the reproduction period of Liza parsia was determined to be in November to March with two peaks in the months of December and February. The maximum GSI values obtained for male and female were 1.49 and 14.71 respectively in the month of February. In December, the gonadosomatic index decreased in female (13.5) and in male (1.4). The average egg diameter of Liza parsia ranged from 0.35 to 0.50 mm. The sex ratio (Male:Female) of the investigated fish was1:1.21. Fecundity of the fish ranged from 18,950 to 1,71,210 during the period of study. Linear relationships between fecundity and total-length, bodyweight, gonad-length and gonad-weight were found and fecundity was more related to the ovary length (r=0.8172) and ovary weight (r=0.8552) than the fish length (r=0.7538) and fish weight (r=0.7592). Keywords: Reproductive characteristics; Liza parsia; GSI; Fecundity DOI: 10.3329/jbau.v8i1.6415J. Bangladesh Agril. Univ. 8(1): 173-178, 2010